What is the Secret to the Success of the US Economy? - Shestakov, Daniil (Journal of Economic Sociology, 2024)
In his book Pavel Usanov argues that the U.S. economy became the world’s largest because the ideas and institutions of Americans were libertarian. However, the government expansions during crises are never fully retracted, leading to a gradual increase in state involvement. The author contends that this growth in government size presents American society with a critical choice: either fundamentally restructure its political system or slide into an all-powerful government and socialism. This review examines the roles of free markets and economic policy in U.S. economic development, drawing on two centuries of macroeconomic history and new economic-historical data. Contrary to the author’s conclusions, I demonstrate that the significant expansion of the public sector in the US did not hinder economic dynamism. In fact, technological progress was most rapid during the “statist” period of 1928-1950. The high average growth rates during this time largely account for the GDP gap between the U.S. and other advanced economies. The review critically assesses the proposed explanations of key events in U.S. economic history, including pre-Civil War financial crises, the economic factors behind the Civil War, the Southern slave economy, late 19th-century protectionism, the causes of the Great Depression, and assessments of Americans’ welfare during World War II. I propose an alternative framework for a libertarian economic history of the US as a history of individual and collective rationality in markets and politics.